Evaluation of Cholangiocarcinoma on MDCT: Varying Imaging Patterns and Preoperative Assessment of Resectability - Therani , Sindhuja; Pulagam , Sindhura; K S Vedaraju; A Mugdha; A Snigdha (Asian Journal of Medical Radiological Research, 2021)
Background: The objectives of our study are to evaluate the various imaging appearances of cholangiocarcinoma and determine the resectability of the tumour on MDCT. Subjects and Methods: Our study is a retrospective study. A search of the case records using the keyword cholangiocarcinoma from the hospital information system yielded 62 patients of cholangiocarcinoma in a period of four years (January 2017 to December 2020). Twelve patients were excluded because of the unavailability of complete records. Study sample was formed by remaining 50 patients. Results: In our institute, hilar cholangiocarcinoma was the most frequent type accounting for 60% (30 patients) followed by distal cholangiocarcinoma accounting for 26% (13 patients) and intrahepatic cholangiocarcinoma was the less common type with 14% (7 patients). Out of 30 patients of hilar cholangiocarcinoma, 23.3% (7 patients) showed mass forming type, 70% (21 patients) showed periductal infiltrating type and 6.6% (2 patients) showed intraductal growing type. Intrahepatic biliary radical dilatation was seen in 92% (46 patients), all patients of hilar and distal cholangiocarcinoma, three patients of intrahepatic cholangiocarcinoma. Portal vein involvement was seen in 34 % (17 patients). Lobar atrophy was seen in 58% (29 patients). Involvement of adjacent liver parenchyma in hilar and distal cholangiocarcinoma was seen in 20% (6 out of 30 pCCA). Out of 21 cases that were taught to be resectable based on the findings of CT 12 cases underwent curative resection and the remaining 9 cases were found to have unresectable tumours giving a positive predictive value of 57.14%. Conclusion: Cholangiocarcinoma is a slow-growing malignant tumour arising from the bile duct epithelium. Most of the cases have poor diagnosis due to late presentation leading to delay in diagnosis and unresectability. Diagnosis of cholangiocarcinoma on imaging can be done by identifying their typical pattern. In our institute, hilar cholangiocarcinoma (periductal infiltrating) was the most frequent type.